Preparation and characterization of CuO nanoparticles with different morphology through a simple quick-precipitation method in DMAC–water mixed solvent - Wu, Rujun; Ma, Zhenye; Gu, Zhenggui; Yang, Yan (Journal of alloys and compounds, 2010)
In this paper, highly dispersed copper oxide (CuO) nanoparticles have been successfully prepared in DMAC–water mixed solvent by a quick-precipitation method. The as-prepared CuO nanoparticles were characterized by high-resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD). Several kinds of CuO particles with different shapes were obtained including panicle-like, spherical-like, spindle-like and rod-like CuO particles. The effects of processing parameters on the size and shape of CuO particles such as the volume ratio of DMAC and water, the adding temperature of NaOH and the molar ratio of Cu 2+ and OH − were investigated. It is found that higher volume ratio of DMAC and water, higher adding temperature of NaOH and higher molar ratio of Cu 2+ and OH − result in smaller size of CuO particles. The nucleation and growth kinetic of the resulting CuO particles were also discussed.